1999
DOI: 10.1097/00000539-199903000-00031
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dexmedetomidine on Neuromuscular Blockade in Human Volunteers

Abstract: We studied the effect of an alpha2-agonist (dexmedetomidine) on rocuronium-induced neuromuscular block during propofol/alfentanil anesthesia. We found that the rocuronium concentration increased and the T1 response decreased during the dexmedetomidine administration. Although these effects were statistically significant, it is unlikely that they are of clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 19 publications
1
28
1
1
Order By: Relevance
“…It can provide muscular relaxation via central pathways without affecting the neuromuscular junction (26). Similarly, we observed the loss of stepping and righting reflexes in rats that received intrathecal dexmedetomidine.…”
Section: Discussionsupporting
confidence: 63%
“…It can provide muscular relaxation via central pathways without affecting the neuromuscular junction (26). Similarly, we observed the loss of stepping and righting reflexes in rats that received intrathecal dexmedetomidine.…”
Section: Discussionsupporting
confidence: 63%
“…A study done by Talke PO et al [43] on the effects of Dexmedetomidine on the neuromuscular blockade the authors showed that dexmedetomidine resulted in a more decrease in the muscle force using mechanomyog-raphy. Although these changes were statistically significant, the investigators concluded that they were not clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…DEX, a selective α-2 adrenoceptor agonist, has sedative, analgesic and anxiolytic effects after intravenous administration (43). DEX also produces dose-dependent HR and blood pressure reductions (44,45).…”
Section: Group ------------------------------------------------------mentioning
confidence: 99%